The Effectiveness of Artificial Intelligence in Improving Capital Market Efficiency in ASEAN: A Systematic Literature Study 2015–2025 - Ela, Nur (GEMA EKONOMI, 2024)
The development of Artificial Intelligence (AI) technology in the capital market is increasingly affecting market efficiency, especially in terms of volatility prediction and price discovery processes. In the ASEAN region, which is experiencing rapid growth in market capitalization, market efficiency is an important factor in maintaining stock market stability and liquidity. This study aims to examine the effectiveness of the application of AI in improving capital market efficiency in ASEAN, focusing on predicting stock volatility and its impact on market liquidity. The method used is a systematic literature review of articles published between 2015 and 2025, which discusses the application of AI in the capital market, particularly in stock volatility prediction and market efficiency indicators. The results show that the application of machine learning (ML) and deep learning (DL) in volatility prediction can improve prediction accuracy and accelerate the price discovery process in the ASEAN capital market. However, its implementation is limited by data infrastructure gaps and regulatory differences between ASEAN countries. The study also found that while AI can improve efficiency, transparent governance is needed to mitigate algorithmic risks that can harm the market. This study suggests policies that support the collaboration of exchanges and fintech to optimize the application of AI in the ASEAN capital market.